2023
DOI: 10.1029/2023jd039501
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Ice Loss, Long‐Term Trends in Extratropical Wave Forcing, and the Observed Strengthening of the QBO‐MJO Connection

Lon L. Hood,
Charles A. Hoopes

Abstract: A modulation has been identified of the tropical Madden‐Julian oscillation (MJO) by the stratospheric quasi‐biennial oscillation (QBO) such that the MJO in boreal winter is ∼40% stronger and persists ∼10 days longer during the easterly QBO phase (QBOE) than during the westerly phase. A proposed mechanism is reductions of tropical lower stratospheric static stability during QBOE caused by (a) the QBO induced meridional circulation; and (b) QBO influences on extratropical wave forcing of the stratospheric residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(140 reference statements)
0
2
0
Order By: Relevance
“…Although the official OMI record only extends back to 1979, a reconstruction of the index back to 1974 using the NOAA PSL OLR data and the 1979-2012 EOFs was performed using the "mjoindices" Python package developed by Hoffmann et al (2021). For the pre-satellite (1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973) period, the same package was applied to the ERA5 OLR data (see, e.g., Hood & Hoopes, 2023; their Section 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the official OMI record only extends back to 1979, a reconstruction of the index back to 1974 using the NOAA PSL OLR data and the 1979-2012 EOFs was performed using the "mjoindices" Python package developed by Hoffmann et al (2021). For the pre-satellite (1959)(1960)(1961)(1962)(1963)(1964)(1965)(1966)(1967)(1968)(1969)(1970)(1971)(1972)(1973) period, the same package was applied to the ERA5 OLR data (see, e.g., Hood & Hoopes, 2023; their Section 2).…”
Section: Methodsmentioning
confidence: 99%
“…Positive feedbacks from below including cloudradiative feedbacks (Sakaeda et al, 2020;Son et al, 2017) and QBO influences on the MJO-induced cold cap anomaly ahead of MJO convection (Hendon & Abhik, 2018;Kodera et al, 2023;Lim & Son, 2020) are likely necessary to explain the full amplitude of the observed modulation. Several studies have found that the QBO-MJO connection has strengthened significantly since the early 1980s, coinciding with long-term decreases in tropical static stability (Hood & Hoopes, 2023;Klotzbach et al, 2019;Sakaeda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%